Study the Variables Affecting Formulation of Ethylcellulose-based Microsponges Loaded with Clobetasol - Ahmed Saad; Lubna Sabri (Iraqi Journal of Pharmaceutical Sciences, 2023)
Clobetasol propionate (CP) is a super potent corticosteroid widely used to treat various skin disorders such as atopic dermatitis and psoriasis. However, its utility for topical application is hampered due to its common side effects, such as skin atrophy, steroidal acne, hypopigmentation, and allergic contact dermatitis. Microsponge is a unique three-dimensional microstructure particle with micro and nano-meters-wide cavities, which can encapsulate both hydrophilic and lipophilic drugs providing increased efficacy and safety. The aim of the current study is to prepare and optimize clobetasol-loaded microsponges. The emulsion solvent diffusion method is used for the preparation of ethylcellulose (EC)-based microsponges. The impact of various formulation variables on microsponge's properties includes; drug: polymer ratio, polyvinyl alcohol (PVA) quantities, the volume of external phase, and stirring rates investigated. The microsponges were characterized in terms of particle size, product yield, CP entrapment %, and in-vitro drug release behavior. The results report that increasing EC concentration led to a significant increase in particle size, with a decrease in product yield and drug entrapment %. Increasing stirring speed or external aqueous volume or PVA w/v % caused a non-significant decrease in production yield and CP entrapment % but showed a significant decrease, and increase in particle size, respectively. Finally, it was concluded that the ability to use ethylcellous as a Msg polymer matrix to prepare uniform, highly porous particles was confirmed by microscope observation and compatibility with CP.